Impact of Work Place Ethics on Employee and Organization Productivity - Kaur, Amandeep (Gyan Management Journal, 2019)
In the present globalised and competitive scenario businesses are expected to function within social,  ethical, and legally accepted principles in our society in order to satisfy their stakeholders. Ethics in  work place has become a very important area for both researchers as well as practitioners. Good ethics  is a good business. Bad ethics can derail even the best organizations. The framework of employment  relationship  necessitates  continuous  interrogation  of  the  complex  issues,  which  arise  from  the  difference  between  productivity  and  employees'  commitment.  This  paper  examines the  effects  of  etiquette and unethical behavior on employee commitment and productivity in India. A descriptive  survey research method was adopted for the study using 100 questionnaires, which were administered  on Employees in different sectors in India. Secondary data as well as documented evidence were used  for the data collection. The sampling procedure was carried out randomly. The data collected were  analyzed through Structural Equation Modeling and supported by descriptive statistics. Each item was  based  on  a  5-Point-  Likert scale.  AMOS  22  was  adopted  in testing the  hypotheses.  The  data  was  presented with the use of SPSS while Structural Equation Modeling (SEM) was utilized. The results  show that significant relationship exists between ethical standards and organizational productivity,  inIndia.
Keywords: Work Ethics; Work Attitudes; Teamwork; Integrity; Self-Discipline; Profitability